Distinct yet linked: chaperone networks in the eukaryotic cytosol - Rospert, Sabine (BioMed Central, 2006)
The terms chaperone and heat-shock protein are frequently used as synonyms, but this is an oversimplification. Although one subset of chaperones is induced by heat stress, a distinct group fails to respond in the same manner. Recent work reveals that this latter group is linked to the translational apparatus and functions in co-translational processes.